Limitations of the Use of Learning Technology in Elementary Schools: Case Study - Wijayanti, Erni; Amalia, Nur (International Conference on Education for All, 2024)
Technology plays an important role in education. Technology and specially designed media can contribute to effective teaching and help students reach their highest potential. Therefore, this researcher aims to analyze the views of school residents regarding the use of technology in classroom learning and describe the factors that cause teachers to not utilize or not use technology-based media in learning. In collecting data, researchers used interview, observation, and docu-mentation techniques and used a technical triangulation model. Based on research results, the factors causing teachers not to utilize technology-based media are the lack of facilities and infrastructure, as well as the lack of internet connection at Balangan State Elementary School.